Caracterização e avaliação do cultivo de arroz em sistema de vazante na baixada Maranhense - Farias Filho, Marcelino Silva (2006)
The agricultural production of Maranhão State come from a large extent of traditional slash-and-burn system practiced by small farmers with shorter fallow period and low biological productivity rates. However another systems less aggressive to the environmental exist at the State how maintenance of food production. The lowland rice cultivation practiced in the Baixada Maranhense is very important amongst the systems. This work aim the report the especifities of this food productive system in Baixada Maranhense, and suggests simple actions that can result in substancial yield improvements and reduce the humans work hardness. From observations realized at the local conditions during two years 2005 and 2006 at three localities where the system occurs. The lost of rice productivity is relationated at plant hidric stress and rodents attack (Arvicola sapidus). The lowland rice cultivation system land increase due the colaps of slash and burn system commum at uplant agriculture. This model of production is supported by the accumulation of organic matter and submerged soils, utilize solar and human energy. It needs of research and technical acts for minimize the constraints that reduce the systems efficiency.